Seasonal variation in contamination of fish flesh of smoked and dried Chrysichthys nigrodigitatus (Lacépède, 1803) with polycyclic aromatic hydrocarbons in the locality of Guessabo (Ivory Coast) - Miessan, Aya Pauline; Aké Assi, Yolande Amoin; Touré, Offianan André; Gooré Bi, Gnamien Willy Taunin (European Scientific Journal, ESJ, 2024)
Polycyclic aromatic hydrocarbons are organic contaminants, some of which are known to be toxic, carcinogenic and mutagenic for humans. These molecules are ubiquitous pollutants of the environment, and can contaminate foodstuffs such as fish. The aim of this study was to assess the level of polycyclic aromatic hydrocarbons contamination in the flesh of a species of freshwater fish, Chrysichthys nigrodigitatus, smoked and dried in the locality of Guessabo. The method used for the determination of these analytes in the matrices was high performance liquid chromatography with UV/Visible detector. Results obtained indicate disproportionate contamination of Benzo(a)pyrene, Benzo(b)fluoranthene, Benzo(a)anthracene and Chrysene molecules depending on the mode of transformation and the season. The highest levels of contamination were recorded during the rainy season in the flesh of Chrysichthys nigrodigitatus smoked for Benzo(a)pyrene (10.39 ± 1.10 µg/kg), Benzo(b)fluoranthene (46.44 ± 3.77 µg/kg) and the sum of the PAH4 (59.88 µg/kg). These levels exceed the standard set by Ivorian regulations (5 µg/kg). In dried fish flesh, a low level of toxicity was recorded whatever the season. There were no significant differences between seasons for most of the molecules studied. The flesh of Chrysichthys nigrodigitatus dried is less contaminated than smoked Chrysichthys nigrodigitatus.